Périglaciaire du Canada : idées nouvelles et perspectives globales - Hamelin, Louis-Edmond (Cahiers de géographie du Québec, 1961)
Periglacial conditions which occur in Canada have been studied recently. Most of the research has been so jar limited in scope (mostly patterned ground and permafrost), undertaken for practical purposes (v.g. airport strips and the new Aklavik's site) and often carried by governmental agencies. Though a hundred titles or so of various articles and notes could be cited in a bibliographical survey of the topic, it must be underlined that the inventory of periglacial phenomena itself is still jar from being completed. This paper, prepared for the Canadian Committee of the International Commission of Periglacial Geomorphology, is based on a broad conception of the topic. The author suggests a useful series of new analytical concepts and outlines new fields for future research.The paper deals with three major aspects of periglacial studies : processes, datation and regions. Some of the processes and conditions are : terrain, wind, vegetation, the climatic « facies » (frozen ground, snow, air temperature and floating ice System). The author feels that all periglacial phenomena in Canada can be classified within a chronological sequence which he makes an attempt to establish as follows : a) Lower and Middle Wisconsin ; b) Pleniwisconsin ; c) Finiwiscon-sin ; d) Late Glacial ; and, e) Recent. Canada, in the opinion of Dr. Hamelin, can be divided into eleven periglacial « provinces  ». The first jour provinces : Elizabeth, Victoria, Keewatin and Innuit are closely associated with continuous permafrost. Three provinces, Hudson, Labrador and Mackenzie, are situated in the periarctic zone. Two, Alberta and Saint-Laurent, have a southern situation along the parallel 50°N. Finally, two provinces : Yukon and Columbia, lie within the limits of Western Cordillera. These eleven provinces are proposed to serve for the designation of periglacial types or regimes throughout the cold regions of the world. The paper concludes with a glossary of new terms suggested for adoption.